What lessons have we learned from Stilfontein? - Kadalie, Bruce (New Agenda: SA Journal of Social and Economic Policy, 2025)
The Stilfontein disaster, which claimed the lives of dozens of informal miners, has become a flashpoint for broader debates about governance, human rights, and economic justice in South Africa. As noted by Lawyers for Human Rights (LHR) the tragedy was not merely an accident but a "direct consequence of systemic neglect and the criminalisation of artisanal miners." The government’s failure to address the dangers of abandoned mines and its punitive approach to artisanal and small-scale mining (ASM) have exacerbated the vulnerabilities of marginalised communities.